The Europeanization of third country judiciaries through the application of the EU acquis: the cases of Russia and Ukraine - Petrov, Roman A.; Kalinichenko, Paul (The international & comparative law quarterly, 2011)
The aim of this article is to look at the phenomenon of Europeanization of judiciaries of third countries through the prism of EU external policy. It is argued that external factors (objectives of EU external policies, EU soft law, EU technical and financial assistance, favourable interpretation of EU law by the ECJ towards third country nationals) play important role in persuading third country judiciaries to apply the EU acquis in their judgments. The similar pattern can be envisaged with regard to Russia and Ukraine. Case study shows that EU policies towards these countries led to generally favourable attitude towards applying the EU acquis by Russian and Ukrainian courts, though mainly as a persuasive source of law. However, problems linked to effectiveness, independence and fight with corruption hinder further Europeanization of judiciaries in Russia and Ukraine.